Diamonds and Dependency: A Case study of Blood Diamond - Muhammad Waseem; Rehan Ashfaq; Zainab Waheed; Maryam Nawaz (Indus Journal of Social Sciences, 2025)
This study focuses on elements of dependency in the movie "Blood Diamond with the lens of Raul Prebisch’s dependency theory in the movie "Blood Diamond”. The study implements qualitative data analysis, guided by the principles of dependency theory. The data for research is collected in the form of dialogues from the movie "Blood Diamond" and the dialogues are discussed in detail with contextual analysis to uncover the elements of dependency. The findings reveal that the film serves as a tool to understand the cycles of exploitation of resources-rich countries by wealthier nations which causes dependency of resource-rich countries on foreign countries. This research is limited to some dialogues related to dependency leaving the room for future researchers for further researches.